IMPLEMENTASI DEVOPS PADA PENGEMBANGAN IMPLEMENTASI SISTEM MONITORING PEMBIMBING TUGAS AKHIR BERBASIS ANDROID - Kurnianti, Apriliya; Al Fauzan, Moch Nurul Indra; Azizah, Laila Ma'rifatul (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Final or thesis is a scientific work written by a student at the time of completing his studies. Problems that arise when working on a thesis include, sometimes students do not have enough time to complete their final assignments, so they have to procrastinate their work; usually there is also a time limit to complete the final project, so students have to work very quickly; And finally, students often feel stressed when they are working on their final assignment. Ineffective use of time, low motivation to excel, student indiscipline, a guidance process that requires face-to-face and also the busyness of lecturers are the main causes of hampering student thesis. During a pandemic like today, face-to-face guidance is greatly minimized. More guidance is done online. However, online guidance also creates new problems, namely chat history that is often deleted or students who forget to document, record the guidance process or even students forget to record the guidance process. Meanwhile, every revision of the guidance must always be recorded on the thesis monitoring sheet. This study aims to design an android-based online final project monitoring system application. The research method uses the DevOps method as a system development method. The results of the study are in the form of an android-based final project monitoring application.